Inhibition of endoplasmic reticulum stress using 4-phenyl butyrate mitigates osteoporosis in a mouse model of hindlimb suspension - Al-Daghestani, Hiba Saad Subhi (2024)
Osteoporosis (OP) characterized by micro-architectural deterioration of bone tissue is a common skeletal disease in the elderly and may lead to fragility fractures. It may also negatively affect implant rehabilitation and prosthesis fixation in the older people. Mouse hindlimb suspension (HLS) is an established model to study disuse- induced OP and its molecular pathology. The disruption of protein folding by endoplasmic reticulum (ER), called ER stress may be a prime driver of OP during disuse. 4- phenylbutyrate (4-PBA) is short chain fatty acid that functions as a chemical chaperone to reduce ER stress. We aimed to investigate the impact of ER stress on OP, and the effect of 4-PBA, as an ER stress inhibitor in the HLS mouse with OP. 21 male C57BL/6J mice were randomly divided into three groups namely: ground-based controls, untreated HLS group, and HLS treated with 4-PBA via intra-peritoneal injections at 100mg/kg/d for 21 days. HLS duration was for 21 days, thereafter, mice were euthanized by cervical dislocation. Humeri, femora, and tibiae bones were collected and cleaned from soft tissues for measurements of reactive oxygen species (ROS) levels, histomorphometry, micro-CT, Raman spectroscopy, and gene expression studies. The results obtained were analysed using GraphPad Prism version 8. High levels of ROS were generated in the hindlimbs (HLs) and forelimbs (FLs) of the untreated HLS group compared to controls. The tibiae bones of the untreated HLS group demonstrated lower osteocyte density, numerous multinucleated osteoclast-like cells, and adipocyte infiltration within the marrow, while micro-CT revealed lower bone volume fraction, reduced trabecular thickness, along with fewer trabeculae striations with increased trabecular separation. Cortical thickness and total cross-section of cortical area were also reduced. Raman spectrophotometric analysis of the femur in the untreated HLS group revealed elevated ER stress with an increase in levels of hydroxyproline, non-collagenous proteins, phenylalanine, tyrosine, and CH2Wag, and a reduction in proteoglycans and adenine. Alkaline phosphatase (ALP) and osteocalcin (OC) expressions were downregulated, while cathepsin K (Cat K), Tartrate resistant Acid Phosphatase (TRAP), and sclerostin were upregulated. Taken together, these characteristics of bone reflect poorer mineralization, less collagen crosslinking, and a pro-inflammatory effect. Treatment with 4-PBA mitigated ER stress levels, restored the normal bone histomorphometry and microarchitecture, increased collagen crosslinking and mineralization, and promoted anti-inflammatory and downregulated bone resorption markers. This study shed light on characterizing the potential contribution of ER stress to OP during bone disuse and the potential effect of 4-PBA as an innovative pharmacological approach to OP treatment.